Direct Acting Antivirals in Patients with Chronic Hepatitis C and Down Syndrome - Eric R. Yoo; Ryan B. Perumpail; George Cholankeril; Aijaz Ahmed (Case Reports in Infectious Diseases)
Patients with Down syndrome who received blood transfusions, likely in conjunction with cardiothoracic surgery for congenital heart disease and prior to the implementation of blood-donor screening for hepatitis C virus infection, face a substantial risk of acquiring the infection. In the past, interferon-based therapy for chronic hepatitis C infection in patients with Down syndrome was noted to have lower efficacy and potentially higher risk of adverse effects. Recently, the treatment for chronic hepatitis C has been revolutionized with the introduction of interferon-free direct acting antivirals with favorable safety, tolerability, and efficacy profile. Based on our experiences, the newly approved sofosbuvir-based direct acting antiviral therapy is well tolerated and highly efficacious in this subpopulation of hepatitis C virus infected patients with Down syndrome.